Exploring the tensions behind the adoption of mobile work practices in SMEs. Issue 5 (7th September 2015) - Raguseo, Elisabetta; Paolucci, Emilio; Neirotti, Paolo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand the contextual conditions under which mobile forms of work are chosen by small and medium enterprises (SMEs) and the most relevant tensions that these firms should be able to face in order to be successful in the adoption of these forms of work. Design/methodology/approach – A survey analysis on 304 SMEs and an analysis of a collection of case studies were conducted to answer to the following research questions: what is the role of contextual conditions in shaping the way firms develop and use their mobile forms of work? Which tensions do SMEs need to manage when adopt a particular mobile form of work? Findings – In this paper, the authors found that SMEs choose different mobile forms of work according to the conditions under which they operate. For example, SMEs that adopt mobile forms of work for operational reasons are more capable of using IT to improve their external orientation. Moreover, the analysis of the configurations of mobile forms of work led to classify in a systematic way the managerial and organizational tensions, and to identify which tensions need to be managed in each mobile work configuration. For example, firms that adopt mobile work given individual employee requests need to manage human resource management tensions. Research limitations/implications – Future research should analyse in depth the jobs that are frequently engaged in mobility and the operational and strategic reasons of their mobility. Moreover, future research should analyse more in-depth companies' capability of managing tensions discussed in this paper. Practical implications – Managers should understand that mobile work is an essential element in the organizational strategy of SMEs, since it is a way to manage more effectively externally oriented business processes. Also policy makers should provide financial support for programmes aimed at promoting the importance of mobile forms of work, since they allow achieving different objectives and saving. Further, demand-oriented policies and experiences about mobile work adoption should be shared. Originality/value – The authors found scant empirical evidence on understanding the contextual conditions under which SMEs choose different mobile forms of work, and the most relevant tensions that SMEs should deal with when they decide for the adoption of a particular mobile work configuration. The value of this paper consists in filling this research gap.